Agricultural science and planning - Yoginder K Alagh (Agricultural Economics Research Review, 2023)
Do agricultural science workers work better in a planning set-up or in an autonomous regime? I am not sure; so, I thought in the half hour of time you have given me—since you are a captive audience—I would share my question with you. My aim is that at the end of this lecture you should at least start thinking about this question.